Association of Renal Function and Menopausal Status with Bone Mineral Density in Middle-aged Women - Sheng, Yueh-Hsuan (Sci Rep, 2015)
The association between mild renal dysfunction and bone mineral density (BMD) has not been fully explored. It is also unclear how menopausal status and the use of Chinese herb affect this association. This is a cross-sectional study that included a total of 1,419 women aged 40 to 55 years old who were recruited from the MJ Health Management Institution in Taiwan between 2009 and 2010. Spinal BMD was assessed by dual-energy X-ray absorptiometry. Renal function was assessed using estimated glomerular filtration rate (eGFR) and creatinine clearance rate (CCr). The multivariable logistic regression and general linear models were employed to assess the association between renal function and BMD. Stratification analyses were performed by menopausal status and use of Chinese herbs. Low CCr levels were significantly associated with low BMD [adjusted odds ratio (AOR) = 1.48, 95% confidence interval (CI) = 1.15–1.90]. This association was observed in premenopausal women (AOR = 1.43, 95% CI = 1.07–1.92) and in women not taking Chinese herbs (AOR = 1.48, 95% CI = 1.14–1.94). CCr is a better predictor for low BMD in middle-aged women. Menopausal status and the use of Chinese herbs also affected this association.